Genes involved in the induction of liver growth by peroxisome proliferators. Issue 5 (7th May 2014) - Amer, Abeer H. A.; Wall, Richard J.; Malla, Sunir; Sang, Fei; Aboobaker, Aziz; Avery, Simon V.; Mellor, Ian R.; Rose, Martin D.; Rowlands, J. Craig; Gant, Timothy W.; Bell, David R.
Graphical Abstract: Abstract: The mechanisms regulating the induction of hepatic DNA synthesis by PPARα agonists are currently incompletely understood, and we set out to determine whether there are different mechanisms of induction for PPARα agonists and other hepatic growth agents. High levels of hepatic DNA synthesis (3–7%) were induced by a PPARα agonist, ciprofibrate, and by a PXRα agonist, cyproterone acetate, and liver samples were taken for transcriptomic analysis in a contemporaneous experiment. Microarray analysis of tissue RNAs detected gene induction at 24 hours after dosing, but failed to detect any biologically plausible response at 1–5 hours after dosing. RNA sequencing of control and ciprofibrate samples at 3 hours after dosing revealed 527 perturbed genes, including known PPARα target genes. Seven candidate genes of interest in regulating cell growth and apoptosis were examined by RT-PCR, and were confirmed to be induced by ciprofibrate treatment. Cyproterone acetate, TCPOBOP and partial hepatectomy induced a distinct spectrum of gene induction for ciprofibrate, demonstrating that ciprofibrate induces DNA synthesis through a unique mechanism. These data show that RNA sequencing is a powerful tool for analysis of differentially induced genes in rat liver, and for identification of candidate genes that mediate the induction of DNA synthesis by PPARα agonists.